The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3748/wjg.v25.i24.3091
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in endoscopic retrograde cholangiopancreatography in Billroth II gastrectomy patients: A systematic review

Abstract: BACKGROUND Endoscopic retrograde cholangiopancreatography (ERCP) in patients with Billroth II gastrectomy has been considered a challenging procedure due to the surgically altered gastrointestinal anatomy. However, there has been a paucity of comparative studies regarding ERCP in Billroth II gastrectomy cases because of procedure-related morbidity and mortality and practical and ethical limitations. This systematic and comprehensive review was performed to obtain a recent perspective on ERCP in Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Finally, we consecutively performed BE-ERCP for patients with Billroth-II reconstruction. However, the effectiveness and safety of side-or forward-viewing endoscope was also reported for ERCP in this population [41]. Considering that Billroth-II is the potential risk factor of obvious perforation during BE-ERCP, further comparative study should be conducted in this setting.…”
Section: Early Adverse Eventsmentioning
confidence: 87%
“…Finally, we consecutively performed BE-ERCP for patients with Billroth-II reconstruction. However, the effectiveness and safety of side-or forward-viewing endoscope was also reported for ERCP in this population [41]. Considering that Billroth-II is the potential risk factor of obvious perforation during BE-ERCP, further comparative study should be conducted in this setting.…”
Section: Early Adverse Eventsmentioning
confidence: 87%
“…The prerequisites of an ideal endoscope are to guarantee safe endoscopic access through the angulated afferent limb and to embody the en face view of the papilla for selective cannulation and therapeutic interventions. Although many experienced endoscopists advocate the routine use of a side-viewing duodenoscope for ERCP in patients with Billroth II anatomy [ 2 , 7 ], previous studies have reported that the incidence of bowel perforation is higher with a side-viewing duodenoscope than with a forward-viewing endoscope [ 5 , 12 ]. Moreover, in a recent meta-analysis, procedure-related mortality occurred exclusively in the side-viewing duodenoscopy group [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although many experienced endoscopists advocate the routine use of a side-viewing duodenoscope for ERCP in patients with Billroth II anatomy [ 2 , 7 ], previous studies have reported that the incidence of bowel perforation is higher with a side-viewing duodenoscope than with a forward-viewing endoscope [ 5 , 12 ]. Moreover, in a recent meta-analysis, procedure-related mortality occurred exclusively in the side-viewing duodenoscopy group [ 12 ]. To guide safe afferent limb navigation, anticipative insertion of a guidewire and catheter into the duodenal stump before duodenoscope advancement was attempted and showed a therapeutic success rate of 81.3–86.3%, a perforation rate of 0.0–1.8%, and procedure-related mortality of 0.0–0.3% in Billroth II gastrectomy patients [ 2 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, ERCP-related adverse events occurred in 25.6% of patients. Previous studies reported the complication rate from 3.5 to 12.4% [ 9 , 11 , 12 , 16 , 18 , 38 40 ]. However, hyperamylasemia was not included in most of these studies.…”
Section: Discussionmentioning
confidence: 99%